The use and effectiveness of wireless network service in UTM colleges - Idrus, Sevia Mahdaliza (Penerbit UTM, 2007)
This chapter presents the analysis of the usage and effectiveness of wireless network services (WNS) in UTM colleges. To maintain a high quality of communication in an infrastructure network, the construction of one or more wireless access points (AP) is necessary. For economic reasons and radio spectrum conversation, AP should be placed well to achieve the optimum coverage region for wireless communication. Hence in this work, the information for building interior database and database for access point (AP) are gathered within College 17, UTM. Performance and measurement analysis has been made in term of signal strength coverage, throughput, transaction rate, lost data and delay within the area. Customer survey has been done to gain response about the service from the respondent. The survey was analyzed to answer questions about where, when, how much, and for what the wireless network is being used. Such information is important in evaluating design principles and planning for future network expansion of the UTM wireless network service at student colleges.